Using a Hybrid Instructional Model in Teaching and Learning - Karen Skibba; Udeme Ndon (Adult Education Research Conference, 2006)
Hybrid courses allow for in-person learning communities combined with the convenience and reflective nature of online learning. This roundtable will provide an opportunity to share educators’ experiences and techniques in implementing the hybrid model to facilitate student learning.
Keywords: Hybrid Instructional Model; Blended Learning